Islamic Values in Building Economic Independence through Entrepreneurship - Sholatiah, Sholatiah; Supriadi, Akhmad; Hidayati, Tri; Erawati, Desi (Universitas Siliwangi, 2025)
Introduction to The Problem: Economic independence is an important aspect in achieving welfare and social stability in society. However, in the realities of modern life, many Muslim individuals and communities still face challenges in achieving economic independence. Unemployment, poverty, and dependence on external aid are still significant problems in many Muslim-majority countries. Based on data obtained from the Central Bureau of Statistics in February 2024, the open unemployment rate reached 4.82%.Purpose/Objective Study: This study aims to explore and analyze the role of Islamic values in building economic independence through entrepreneurship.Design/Methodology/Approach: This research uses a qualitative approach with a descriptive method and incorporates literature study, as well as analysis of relevant data.Findings: The results show that the application of Islamic values not only enhances the reputation and credibility of entrepreneurs, but also promotes sustainable and inclusive economic growth. Moreover, these values assist entrepreneurs in overcoming business challenges with high integrity and ethics. The study concludes that the integration of Islamic values in entrepreneurship has great potential to build economic independence, strengthen local communities, reduce economic dependency, and achieve social welfare. Practical implications of the findings include the need for Islamic values-based entrepreneurship education and training in the modern economy as well as the development of sharia-compliant business models.Paper Type: Research Article